Moyamoya Disease in Pregnancy: Management after Intracranial Bypass Grafting. (25th March 2012) - Gimovsky, A. C.; Macri, C. J.; Bathgate, S. L.; Ross, D. E.
Abstract : Moyamoya disease (MD) is a chronic, progressive cerebrovascular disease distinguished by bilateral stenosis or occlusion of the arteries around the circle of Willis with resulting prominent arterial collateral circulation. We describe a pregnant woman in whom this diagnosis was confirmed by cerebral angiogram and treated with bilateral superficial temporal artery-middle cerebral artery (STA-MCA) bypass grafting prior to conception. The patient was managed with strict blood pressure monitoring and low-dose aspirin antepartum, intrapartum, and postpartum. The patient presented in spontaneous labor at term and underwent a spontaneous vaginal delivery without complications.